Project identification phase :
The results of this phase will be highly dependent on the type of solution being provided – whether it is aproduct, process, or system that is being delivered. It is important that testing be done in accordance with the expectations of the community partner and other stakeholders. However, testing should also be done with best practices and your professional engineering ethics in mind.